Limb derived cells as a paradigm for engineering self‐assembling skeletal tissues. (17th September 2017) - Fernando, Warnakulasuriya A.; Papantoniou, Ioannis; Mendes, Luis F.; Hall, Gabriella Nilsson; Bosmans, Kathleen; Tam, Wai L.; Teixeira, Liliana M.; Moos, Malcolm; Geris, Liesbet; Luyten, Frank P.
Abstract: Mimicking developmental events has been proposed as a strategy to engineer tissue constructs for regenerative medicine. However, this approach has not yet been investigated for skeletal tissues. Here, it is demonstrated that ectopic implantation of day‐14.5 mouse embryonic long bone anlagen, dissociated into single cells and randomly incorporated in a bioengineered construct, gives rise to epiphyseal growth plate‐like structures, bone and marrow, which share many morphological and molecular similarities to epiphyseal units that form after transplanting intact long bone anlage, demonstrating substantial robustness and autonomy of complex tissue self‐assembly and the overall organogenesis process. In vitro studies confirm the self‐aggregation and patterning capacity of anlage cells and demonstrate that the model can be used to evaluate the effects of large and small molecules on biological behaviour. These results reveal the preservation of self‐organizing and self‐patterning capacity of anlage cells even when disconnected from their developmental niche and subjected to system perturbations such as cellular dissociation. These inherent features make long bone anlage cells attractive as a model system for tissue engineering technologies aimed at creating constructs that have the potential to self‐assemble and self‐pattern complex architectural structures.